2020
DOI: 10.1371/journal.pone.0229110
|View full text |Cite
|
Sign up to set email alerts
|

Spatial networks differ when food supply changes: Foraging strategy of Egyptian fruit bats

Abstract: Animals are faced with a range of ecological constraints that shape their behavioural decisions. Habitat features that affect resource abundance will also have an impact, especially as regards spatial distribution, which will in turn affect associations between the animals. Here we utilised a network approach, using spatial and genetic data, to describe patterns in use of space (foraging sites) by free-ranging Egyptian fruit bats (Rousettus aegyptiacus) at the Dakhla Oasis in Egypt. We observed a decrease in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 85 publications
0
16
1
Order By: Relevance
“…Selection of roosts with high betweenness may facilitate access to information in a similar manner as proposed for the tree‐roosting giant noctules ( Nyctalus lasiopterus , Fortuna et al ., 2009). Moreover, as spring is the season of scarce food resources, we propose that multiple core roosts during this season may be beneficial for information transfer regarding suitable foraging sites (Bachorec et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selection of roosts with high betweenness may facilitate access to information in a similar manner as proposed for the tree‐roosting giant noctules ( Nyctalus lasiopterus , Fortuna et al ., 2009). Moreover, as spring is the season of scarce food resources, we propose that multiple core roosts during this season may be beneficial for information transfer regarding suitable foraging sites (Bachorec et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we propose that these ‘socially exploratory’ fruit bats are likely to play an important role in connecting and providing valuable information to individuals that do not roost together (Whitehead, 2008; Chaverri, 2010; Farine & Whitehead, 2015). Though we have no evidence for information transfer, we presume that association with and/or following of these central individuals may facilitate access to public information on roosting or foraging sites (Bachorec et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to change between years due to births, deaths, dispersal, and addition of tagged bats. We chose to construct these networks based upon the entire maternity season because our goal was to use intraroost networks to evaluate cohabitation networks, which are typically based on seasons (Bachorec et al, 2020;Chaverri, 2010) or years (Kerth et al, 2011;Wilkinson et al, 2019). Data collected from Mammoth readers in 2017 were not included because antennas were placed in areas within the roost that few bats visited, and antennas were relocated in 2018.…”
Section: Data Collectionmentioning
confidence: 99%
“…These studies found that time of emergence and return to day roost sites also varied according to season, age, sex, and depended on the intraspecific variation in a range of ecological parameters. The availability of food is an important component in this relation and Lučan et al (2016) and Bachorec et al (2020) have shown a negative correlation between fruit bat home range and food availability. Similar relations have been noted in other groups of mammals, for example, the rodent Octodon degus (Molina, 1782) (Octodontidae), which spent more time outside their burrows foraging during the nonreproductive period because of food scarcity compared to breeding period (Ebensperger and Hurtado 2005).…”
Section: Introductionmentioning
confidence: 99%